Evaluation of some Gernada land for agricultural use, Libya - Elkhboli, M.M.H.; Ali, A.M.; Saleh, S.A. (Al-Mukhtar Journal of Sciences, 2008)
The study was carried out at Gemada village during 2004/2005 season, where 21 soil samples were collected. MicroLEIS 2000 software was used to evaluate productivity of agricultural lands and its suitability for some agricultural crops. The evaluation of soil productivity classified the soils in the third class (S3) and the unsuitable (N), the most obstacles were soil erosion, slope and bio-climate. Land assessment for agricultural use and its suitability to grow wheat, maize, melon, peaches and olive showed that the most limiting factors were; soil texture, calcium carbonate and profile development. GIS Arc View 3.2 was used to connect the data that had been collected from the field, laboratory and land evaluation with its spatial (geographical) sites to produce land use and soil productivity maps for the study area.